Role of the platelet-activating factor (PAF) receptor during pulmonary infection with gram negative bacteria - Soares, A C (2002)
1. The lipid mediator PAF plays an important role in the phagocytosis of particles, including bacteria, and consequent production of pro-inflammatory cytokines, such as TNF-α and IL-8. 2. Using a PAF receptor antagonist (UK-74,505) and PAF receptor knock-out mice, we have investigated the relevance of PAF for the inflammatory changes and lethality after pulmonary infection with the gram-negative bacteria Klebsiella pneumoniae in mice. 3. At an inoculum of 3×10(6) bacteria, there was marked pulmonary (bronchoalveolar lavage and lung) neutrophilia that started early (2.5 h after infection) and peaked at 48 h. All animals were dead by day 4 of infection. The chemokine KC and the pro-inflammatory cytokine TNF-α increased rapidly and persisted for 48 h in the lungs. 4. Pretreatment with UK-74,505 (30 mg kg(−1) per day, p.o.) had no significant effects on the number of infiltrating neutrophils in BAL fluid or lung tissue, as assessed by histology and measuring myeloperoxidase, or on the concentrations of KC. In contrast, concentrations of TNF-α and the number of bacteria inside neutrophils were significantly diminished. 5. In order to support a role for the PAF during K. pneumoniae infection, experiments were also carried out in PAFR-deficient mice. In the latter animals, lethality occurred earlier than in wild-type controls. This was associated with greater number of bacteria in lung tissue and diminished percentage of neutrophils containing bacteria in their cytoplasm. 6. Our results suggest that PAF, acting on its receptor, plays a protective role during infection with K. pneumoniae in mice.